1983
DOI: 10.1115/1.3245618
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Prediction of Wall Temperatures for Near-Critical Para-Hydrogen in Turbulent Upflow Inside Vertical Tubes

Abstract: Presented herein is a method of including density fluctuations in the equations of turbulent transport. Results of a numerical analysis indicate that the method may be used to predict heat transfer for the case of near-critical para-hydrogen in turbulent upflow inside vertical tubes. Wall temperatures, heat transfer coefficients, and velocities obtained by coupling the equations of turbulent momentum and heat transfer with a perturbed equation of state show good agreement with experiments for inlet reduced pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…12,13 Several numerical studies with turbulence models have also been performed for supercritical flows to test the applicability of various turbulence models to heat transfer problems regarding SCP fluids. These studies include Bellmore and Reid, 14 Koshizuka et al, 15 and He et al 16 but their results were not always successful. More advanced computational studies using direct numerical simulation ͑DNS͒ have been recently conducted to investigate the heat transfer at SCP.…”
Section: Introductionmentioning
confidence: 96%
“…12,13 Several numerical studies with turbulence models have also been performed for supercritical flows to test the applicability of various turbulence models to heat transfer problems regarding SCP fluids. These studies include Bellmore and Reid, 14 Koshizuka et al, 15 and He et al 16 but their results were not always successful. More advanced computational studies using direct numerical simulation ͑DNS͒ have been recently conducted to investigate the heat transfer at SCP.…”
Section: Introductionmentioning
confidence: 96%
“…As a pioneer work, Bellmore and Reid [17] suggested a modified mixing length model by including density fluctuations into the equations of turbulent transport. The additional terms owing to density fluctuations into the time-averaged turbulent continuity equation added to the difficulty in solving the flow field.…”
Section: Introductionmentioning
confidence: 99%
“…First, based on the assumption that the effects of buoyancy and acceleration are negligible, the convection transport equations for the steady turbulent compressible pipe flows are reduced into the one-dimensional boundary-layer equations and then nondimensionalized. Second, on the basis of the work by Bellmore and Reid [17], a new approach to include density fluctuations in the equations of turbulent transport is suggested, and then a modified mixing length turbulence model is developed for the variable property flow. Finally, with these mathematical models, numerical calculations are performed to simulate the turbulent convective heat transfer of water flowing in round tubes at supercritical pressures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valueva and Popov [1985] showed that this model resulted in good agreement to subcritical and supercritical flows. On the other hand, Bellmore and Reid [1983] suggested a mixing length model with density fluctuation term, which was derived from the Reynolds-average technique rather than from the Favre-average technique. Lee and Howell [1998] modified this model and showed that their results were in a good agreement with some data.…”
Section: Introductionmentioning
confidence: 99%